Konsep Pengambilan Keputusan oleh Triumvirat Pelaksana Tugas Kepresidenan jika Presiden dan Wakil Presiden Berhalangan Tetap (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines the decision-making concept that should guide the triumvirate of ministers who temporarily exercise presidential duties when both the President and Vice President are permanently unable to serve. The issue is significant because Article 8 paragraph (3) of the 1945 Constitution designates the Minister of Foreign Affairs, the Minister of Home Affairs, and the Minister of Defense to act together, yet no detailed statutory framework has clarified the institutional procedure for joint decision-making. Using normative juridical research, the article analyzes constitutional provisions, presidential regulations concerning the three ministries, and decision-making theory. The study finds that the legal basis for the triumvirate exists only at the constitutional level and that the absence of derivative regulation creates uncertainty regarding coordination and the method for taking binding decisions. The article argues that, in the absence of specific rules, decisions should be structured through division of functions, deliberation, and, if necessary, voting as a mechanism to resolve deadlock, but a formal statutory framework remains urgently needed.